IDENTIFIKASI JENIS TUPAI (Tupaia Sp.) DI HUTAN TEMBAWANG DESA MENSIKU BERSATU KECAMATAN BINJAI HULU KABUPATEN SINTANG - Anggara, Gayus; Nurdjali, Bachrun; AM, Iskandar (JURNAL HUTAN LESTARI, 2017)
Forest ecosystem and flora and fauna variety are a basic capital for national development which benefit for human’ s life in particular at Tembangan forest located in Mensiku Bersatu village of Binjai Hulu sub-district of Sintang.  Tembangan forest located in Mensiku Bersatu village of Binjai Hulu sub-district of Sintang has a lot of flora and fauna and one of its familiar animals is squirrel. For several reasons, squirrel conservation is considered as an unimportant action since this wild animal is often regarded as one of potential pests. In fact, squirrel has several significant roles in maintaining the sustainability of forest ecosystem since this animal can perform as a flora distributor or a insect controller that distribute seeds around Tembangan forest. The purpose of this study is to investigate the type of squirrel species at Tembangan forest located in Mensiku Bersatu village of Binjai Hulu sub-district of Sintang. The study result is expected to have significant contribution regarding the required data for management, protection, and conservation of Tembangan forest.  The setting of this study is in Tembangan forest located in Mensiku Bersatu village of Binjai Hulu sub-district of Sintang. Survey method and purposive sampling technique are applied in this study to identify the squirrel’s main territory around Tembangan forest. Based on the results of observation and identification, it can be concluded that Tembangan forest located in Mensiku Bersatu village of Binjai Hulu sub-district of Sintang has 5 species of squirrel specifically Spotted Squirrel (Tupaica picta), Slim Squirrel, (Tupaica gracilis), Small Squirrel (Tupaica minor), Javan Treeshrew Squirrel (Tupaica javanica),and Beautiful Squirrel (Tupaica splendidula). There are approximately 183 squirrels living in Tembangan forest and Spotted Squirrel (Tupaica picta) is the most common type of squirrel found in there and Tembangan forest has 82 spotted squirrel (Tupaica picta), 36 slim squirrels (Tupaica gracillis), 45 small squirrels (Tupaica minor), 13 Javan Treeshrew Squirrel (Tupaica javanica), and 7 beautiful squirrels (Tupaica splendidula). Keywords: Identification of squirrel type, Mensiku Bersatu village, Tembangan forest